2007
DOI: 10.1123/pes.19.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic-Exercise Training Improves Ventilatory Efficiency in Overweight Children

Abstract: The objective of this study was to investigate the effect of an 8-week aerobic-exercise training program on ventilatory threshold and ventilatory efficiency in overweight children. Twenty overweight children (BMI > 85th percentile) performed a graded cycle exercise test at baseline and were then randomly assigned to 8 weeks of stationary cycling (n = 10) or a nonexercising control group (n = 10). Ventilatory variables were examined at ventilatory threshold (VT), which was determined via the Dmax method. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 19 publications
3
26
0
1
Order By: Relevance
“…Regular physical activity and nutritional guidance are among the therapeutic actions used to reduce metabolic syndrome in adults [5][6] . Exercise and nutritional interventions seem to be a suitable, if not ideal, therapy for metabolic syndrome 5 , because aerobic exercises 7 and weight loss [8][9][10] modulate insulin sensitivity 5 and influence cardiovascular risk factors 1,[11][12][13] . Although exercise is an important factor influencing metabolic syndrome and obesity [5][6] , only a few interventional studies have applied exercise as therapeutic treatment for children 3 and adolescents [5][6][7][8][9][10][11][12][13][14] with cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Regular physical activity and nutritional guidance are among the therapeutic actions used to reduce metabolic syndrome in adults [5][6] . Exercise and nutritional interventions seem to be a suitable, if not ideal, therapy for metabolic syndrome 5 , because aerobic exercises 7 and weight loss [8][9][10] modulate insulin sensitivity 5 and influence cardiovascular risk factors 1,[11][12][13] . Although exercise is an important factor influencing metabolic syndrome and obesity [5][6] , only a few interventional studies have applied exercise as therapeutic treatment for children 3 and adolescents [5][6][7][8][9][10][11][12][13][14] with cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…13 Kaufman C et al studied the effect of aerobic training on ventilatory efficiency in overweight children, and found that the training helped to reverse the decrements in cardiopulmonary function observed over a period of time in overweight children. 14 Bharali R et al studied the effect of aerobic exercises in 100 medical students and concluded that the spirometric variables increased after acute exercise and the values were higher in boys than in girls. 15 Shashi M, et al in a study conducted on Punjab young male adults concluded that regular exercise enhances physical capabilities and physiological responses of the human body and the lungs are no exception.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the respiratory function abnormalities seen in obesity are due to the mechanical load of adipose tissue on the chest wall and also muscular imbalances-associated with inactivity imposing restriction on the thorax (16), So any weight-loss training (fat loss) may compensate for this situation; furthermore, the improvement of the respiratory muscles is another beneficial effect of regular exercise training (17). Exercise improves lung function by enhancing the exchange of gasses in the alveoli and elevating the absorption of oxygen from the bloodstream (9,12,15). In obese individuals, the hyper-responsiveness to exercise may be explained by three hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that Regular physical activity of adequate intensity and duration can result in a number of potential beneficial effects on general health (8). However, obese adolescence tend to show less tolerance to daily activities and exercise due to sedentary lifestyle and therefore be inclined to have lower aerobic fitness and consequently lower pulmonary functions than their normal peers (9,10). If these exercises are done at schools, the synergy caused by peers can result in better tolerance of exercise intensity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation